Student Emotions in the Shift to Online Learning During the COVID-19 Pandemic - Espino, Danielle P.; Wright, Tiffany; Brown, Victoria M.; Mbasu, Zachariah; Sweeney, Matthew; Lee, Seung B. (Advances in Quantitative Ethnography, 2021)
The COVID-19 pandemic saw sudden measures to stop the spread of the virus, closing schools and forcing a shift to remote learning. This study examines the emotions exhibited by students around factors of online learning as they transitioned abruptly from in-person instruction. Student responses to a New York Times writing prompt in March 2020 were analyzed using frequencies and epistemic network analysis (ENA) models. About half of the responses contained positive emotional valence, but more than three quarters had negative emotional valence. The strongest connection was observed between negative emotional valence for instructional format and focus. More specifically, anxiety between the format, focus, and workload were strongly connected, indicative of the difficulties faced by students to maintain focus and balance assignments on learning activities while being at home. At the same time, there was a significant connection between positive and negative emotional valence regarding the instructional format, attributed to mixed and changing emotions with adjusting to online learning. When students did exhibit positive emotions, it was interest in the instructional format linked with interest in schedule, indicating that the scheduling flexibility of the online format was the factor students liked most.